A motivational model of employee attachment to an organization - Gagné, Marylène; Howard, Joshua L (Edward Elgar Publishing, 2016)
This Handbook provides an up-to-date review of theory and research pertaining to employee commitment in the workplace, outlining its value for both employers and employees and identifying key factors in its development, maintenance or ...